Improved tensile and impact responses of microcellular PP/γ-irradiated elastomer blends corroborating microstructure and crystallinity. Issue 12 (2nd December 2021) - Dutta, Anindya; Banerjee, Debjyoti; Ghosh, Anup K.
Abstract: The purpose of the present study was to compare the tensile and impact performances of foams of PP/γ-irradiated elastomer blends with that of the foams of PP/unirradiated elastomer blends. Furthermore, the morphological and crystallinity studies were considered to correlate the tensile and impact behavior of foams. Foaming of blends was carried out in a batch foaming set up with supercritical CO2 . A continuous decrease in crystallinity was observed for both types of blends along with the relative change in the number of different crystal forms. Remarkable necking phenomenon and strain-induced crystallization were observed in foams. The tensile modulus of samples significantly increased up to 3 times than that of the neat samples at lower temperature foaming. The maximum modulus of foams was attained for the blends with 10% irradiated elastomer concentration. The impact strength of foam was also improved at the same condition, where the tensile modulus was highest. Graphical Abstract: UF0001